The Impact of the Government Revolution 4.0 on District Integrated Administration Service (DIAS) - Karno Karno; Andi Masrich; Afif Syarifudin Yahya; Afni Nooraini (JURNAL ILMU SOSIAL, 2020)
The government is required to manage the government system to achieve the state’s goals as guaranteed by the Republic of Indonesia’s constitution. The management of a government system requires fundamental changes through the Government Revolution 4.0 approach. One form of the government revolution is the District Integrated Administration Service (DIAS) in Cibitung District of Bekasi Regency. However, not all DIAS has made fundamental changes with the Government Revolution 4.0 approach. This research aimed to find out and analyze the government revolution in DIAS in Cibitung District, Bekasi Regency. The study used a mixed-method between quantitative and qualitative methods. The data collection used is closed questionnaires and open questionnaires with a total sample of 49 respondents. The data analysis used is Structure Equation Model (SEM) of Lisrel and Microsoft Excel. The research found that the District Integrated Administration Service in the Government Revolution 4.0 has an average value of 6.80 for positive factors and 5.20 for negative factors. The results are due to weaknesses, namely recurring problems, system failures, complaints, and delays in service. Moreover, the government revolution had a positive impact of 74.83% and a negative impact of 25.17%, hence categorized as “good”. The study concludes that the District Integrated Administration Service acquire the category of “not yet star service”, thus requires a solution for weakness factors.